Aplikasi Tracking Pedagang Keliling Dengan GPS Google Maps API Berbasis Android - Yunita Sari; Hardi Riyansah (Fakultas Teknik Universitas Persada Indonesia YAI, 2021)
Food / snacks are the primary needs of every human being. As a primary need, food must besufficiently available at all times, safe, of high quality, and of various types and of course at aprice that is affordable to the purchasing power of the community. business, sometimes asconsumers we have difficulty finding the exact location of the traveling merchants who are aroundwhere we live. Taking advantage of technological advances today, more and more smartphoneusers. Of the many smartphone users, the operating system that has many users is Android.Android-based smartphones are very easy to use, so many people choose to use Android-basedsmartphones. Along with the development of science and technology, there is a technologydevelopment, namely GPS (Global Positioning System). Google Maps API. The Google MapsAPI is a form of service from Google that offers the latest mapping technology that can be usedfor various needs.